Markov switching regimes in a monetary exchange rate model - Michael Frömmel; Ronald MacDonald; Lukas Menkhoff (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2002)
This paper extends the real interest differential (RID) model of Frankel (1979) by introducing Markov regime switches for three exchange rates over the years 1973 - 2000. Evidence of a non-linear relationship between exchange rates and underlying fundamentals is provided. One of the regimes represents exactly the RID case. Decisive fundamentals in determining regimes turn out to be mainly interest rates. The established relationship is shown to be stable in several respects: regimes are highly persistent, provide a much better description of the data than alternatives and are robust towards several modifications.
Keywords: F31; 330; Markov switching model; monetary model of the exchange rate; real interest differential (RID) model (Frankel 1979); Monetäre Wechselkurstheorie; Zinsdifferenz; Markovscher Prozess; Schätzung; Theorie; Welt